Lessons from iPSC research: insights on peripheral nerve disease - Mittal, Kritika; Schrenk-Siemens, Katrin (Neuroscience letters, 2020)
With the publication of their breakthrough discovery describing the induction of pluripotent stem cells (iPSCs) from mouse and human fibroblasts, Takahashi and Yamanaka have changed the scientific landscape. The possibility of deriving human pluripotent stem cells from almost any somatic cell has provided the unprecedented opportunity to study specific hereditary diseases in human cells. In the context of diseases affecting peripheral nerves, iPSC platforms are now being increasingly utilized to investigate the underlying pathology as well as regenerative strategies. Peripheral neuropathies result in peripheral nerve damage, leading to - among other things - the degeneration of affected nerve fibers accompanied by severe sensory, motor and autonomic symptoms, often including intense pain. The generation of iPSCs from hereditary forms of peripheral neuropathies and their directed differentiation into cell types most affected by the disease can be instrumental to better understanding the pathological mechanisms underlying these disorders and to investigating cell replacement strategies for repair. In this minireview, we highlight studies that have used iPSCs to investigate the therapeutic potential of iPSC-derived Schwann cell-like cells for nerve regeneration, as well as studies using patient iPSC derivatives to investigate their contribution to disease pathology.
Gesehen am 18.11.2020